Systemically and cutaneously distributed ectoparasiticides: a review of the efficacy against ticks and fleas on dogs. Issue 1 (December 2016) - Pfister, Kurt; Armstrong, Rob
Abstract Acaricidal (tick) and insecticidal (flea) efficacy of systemically and cutaneously distributed ectoparasiticide products for dogs are compared based on permethrin and fluralaner as representative molecules. Results of efficacy studies against fleas and ticks are reviewed that show generally good to excellent results. Both externally and systemically distributed treatments have benefits and weaknesses in potentially preventing pathogen transmission by these arthropod vectors. Four general properties are considered related to the goal of providing optimal reduction in the risk of vector-borne pathogen transmission. These are:1. Owner adherence to the recommended treatment protocol; 2. Rapid onset of activity following administration; 3. Uniform efficacy over all areas of the treated dog at risk for parasite attachment; 4. Maintenance of high efficacy throughout the retreatment interval. In considering these four factors, a systemically distributed acaricide can offer an option that is at least as effective as a cutaneously administered acaricide with regard to the overall goal of reducing the risk of vector-borne pathogen transmission.